Total conversion mods: expanding beyond the original game - Markocki, Miłosz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The goal of this article is to outline selected aspects of the phenomenon of game modding, with particular emphasis on mods known as total conversion mods. The text mentions the features of such mods which are both fundamental and most characteristic, in order to establish the necessary context for further discussions concerning the differences between total conversion mods and other types of mods. The article aims to address the question of the legitimacy of approaching total con- version mods as independent text by presenting the most important features of such mods and their application and discussing how they function in the chosen example, i.e. ST: New Horizons, so that the following question may be posed: Do the changes introduced to the original game’s gameplay and mechanics in a given conversion mod justify regarding it as a separate game text?